Key Points Concerning Amyloid Infectivity and Prion-Like Neuronal Invasion - Espargaró, Alba; Busquets, Maria Antònia; Estelrich, Joan; Sabate, Raimon (Frontiers in Molecular Neuroscience, 2016)
Amyloid aggregation has been related to an increasing number of human illnesses, from Alzheimer and Parkinson’s diseases to Creutzfeldt-Jakob disease. Traditionally only prions have been considered as infectious agents with a high capacity of propagation. Although recent publications have showed that many amyloid proteins, including amyloid β-peptide, α-synuclein and tau protein, also propagate in a “prion-like” manner, the link between propagation of pathological proteins and neurotoxicity has not been evidenced. The extremely low infectivity in natural conditions of the most of non-prion amyloids is far from the spreading capacity displayed by the prions. However, it is important to elucidate the key factors that cause non-prion amyloids become infectious agents. In recent years, important advances in the understanding of the amyloid processes of amyloid-like proteins and unrelated prions (i.e., yeast and fungal prions) have yielded essential information that can be applied to shed light on the prion phenomenon in mammals and humans. As shown in this review, recent evidences suggest that there are key factors that could dramatically modulate the prion capacity of proteins in the amyloid conformation. The concentration of nuclei, the presence of oligomers, and the toxicity, resistance and localization of these aggregates could be key factors affecting their spreading. In short, those factors that favor the high concentration of extracellular nuclei or oligomers, characterized by a small size, with a low toxicity could dramatically increase prion propensity; whereas low concentrations of highly toxic intracellular amyloids, with a large size, would prevent infectivity.